PERBEDAAN HASIL BELAJAR FISIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER BERBANTU LEMBAR KEGIATAN SISWA DENGAN MODEL PEMBELAJARAN LANGSUNG PADA MATERI POKOK OPTIK GEOMETRI - Rappel Situmorang (Universitas Negeri Medan, 2013)
This study aims to determine the differences in physics learningoutcomes using cooperative learning model Numbered Heads Together Sheet-assisted Student Activity with direct instruction model in the subjectmatter Geometric Optics in Class X Semester 2 SMAN 7 T.P. 2012/2013. The population in this study were all students of class X consists of 9 parallelclasses. The study sample comprised 2 classes taken by cluster randomsampling is a class X-3 as a class experiment given cooperative learningmodel Numbered Heads Together Student Activity Sheet assisted and X-9 asa control class with direct instructional model, each of which consists of 40students. Pretest data obtained average value is the experimental class andcontrol class 34.90 is 37.10. After being given a different treatment to thesecond class, the average values obtained posttest for the experimental classwas 73.20 and 66.80 control class. The results of testing hypotheses obtainedt-test = 2.78 and t-table = 1.99 at significance level α = 0.05 and df = 78, ttest>t-table. It showed no significant difference in the learning outcomes of students using cooperative learning model Numbered Heads Together Sheet assisted Student Activity with learning model directly in the subject matterOptical Geometry in class X Semester 2 SMAN 7 T.P. 2012/2013.